Decolonisation and Downshift-Knowledge Reproduction in Africa - Adegbite Simon Aboluwoye (Journal of BRICS Studies)
Colonialism established a system of racial oppression, both mentally and physically, by impeding pre-colonial African education, which was originally intended to reflect the realities of pre-colonial African societies. Before the colonial administration, Africans were already developed people with different educations for different age groups, making them functional and inclusive within the larger political sphere. Decolonisation only reflects a shift in political power and the withdrawal of colonialists from African territories, but it has not resulted in any fundamental shift in the mentality of political leaders and nation-building in the decolonised nations. The education curriculum left behind by colonial governments was designed to make African nations economically and technologically dependent on developed nations. Such a pattern of education was not geared toward African technological development, but rather conditioned African nations to be consumers rather than producers, with the resulting loss of initiative among the Africans. The curriculum is insidious in terms of principles and implementation across all levels of educational institutions, slowly destroying the economies of African nations that were once ahead of European nations during the pre-colonial epoch. Instead of accelerating the socio-economic development of decolonised African nations, the curriculum based on Western principles and ideas further subjugates African economies to imperialist influence and hegemony through the instrumentality of international financial institutions, which frequently dictate exploitative asymmetric relationships between the developed and developing African nations. African nations must therefore look inward for an African-oriented and culturally appropriate educational curriculum to meet the demand for socioeconomic advancement and growth.